Forestry Sciences and their relationship with justice - Arce Rojas, Rodrigo Severo (2022)
This article deals with the relationship between forestry sciences and justice with the aim of enriching the theoretical and operational framework of forestry sciences and of contributing to a better relationship between society and its forests. For this purpose, a specialized bibliographic review is carried out and complemented by contrasting it with the forestry reality in Peru. This shows that -from a forestry discipline perspective- forestry sciences consider that they do not have much to do with the issue of justice, which would correspond to other fields of knowledge. However, different types of justice are an integral part of their theory and practice when forests are understood as socio-ecosystems, a product of coupled systems that include forests, society and culture. The strongly anthropocentric conception of forestry science, which translates into public administration and forestry operations, makes ecological justice invisible. Other more human-related justice such as cognitive/epistemic justice or linguistic justice are absent.